Analisis Manajemen Pengelolaan Koperasi Pesantren dalam Mewujudkan Kemandirian Pesantren Ummul Ayman Samalanga - Amrullah Amrullah (Tadabbur: Jurnal Peradaban Islam, 2019)
In the era of the demands of scientific and technological development, the development of competence and capacity of santri is a must. Many pesantren have sought to develop productive economic activities. The number of Kopontren in Indonesia for many years is growing. One of the pesantren that began to move independently in economic activities is Pesantren Ummul Ayman Samalanga. There are 14 units of pesantren business that are all incorporated in the container board. The existence of various business units is a means of education in the field of independence, entrepreneurship, sincerity, and sacrifice. To maximize this, it is necessary management of pesantren cooperative management which is effective, efficient, and professional in its management. Therefore, this research would like to study about how management of pesantren cooperative in realizing the independence of Pesantren Ummul Ayman Samalanga. The methodology used in this research is qualitative research. The research process is done in field research (field research). The results showed that the management (Management) Ummul Ayman Pesantren Cooperative consists of: planning (planning) based on Pondok value; organizing (Organizing) organizing; transformative collective leadership; total quality control based centralized centralized finance. As for its implementation, the characteristics of the management encourage the establishment of economic independence of Ummul Ayman Samalanga pesantren.